Modeling techniques for kinematic analysis of a six-axis robotic arm. (July 2019) - Guida, R; De Simone, M C; Dašić, P; Guida, D
Abstract: The purpose of this analysis is to evaluate the effectiveness of different modeling techniques for a COMAU six-axis robot arm. The robot manipulator represents one of the most used robots in the mechanical industry. For robots, with a high number of degrees of freedom, to obtain a kinematic model, Denavit-Hartemberg parameters allow representing geometric transformations in the Euclidean space through the minimum number of parameters. Furthermore, the use of detailed multibody models and the use of sophisticated tools like the Robotics Toolbox System, allow performing, in a very efficient way, inverse kinematic analysis and trajectory planning to control the robot move from one configuration to another.